PERBAIKAN TEGANGAN PENYULANG KARUMBU DENGAN METODE PECAH BEBAN PADA PT. PLN (PERSERO) ULP WOHA - YASYFIN NUR MUHAMMAD; Indra Darmawan; Titi Andriani; Muhammad Hidayatullah (Jurnal Altron, 2023)
The electrical energy that is distributed to customers is connected to the distribution network. Within the scope of the electricity distribution network, there are problems, namely the rating capacity that exceeds the feeder load and the length of the network on the feeder. This is dangerous because the load being served is too far away, and the excessive load will increase the current flowing through the conductor. so that it causes the voltage to drop to the customer, and if there is a feeder disturbance, it will expand the blackout area. Power loss is a problem that has always been faced by PT. PLN (Persero) and is unavoidable. This is also similar to the conditions that occurred at PT. PLN (Persero) ULP Woha, where the load on the Karumbu feeder is too heavy with a capacity of up to 91 amperes and a feeder length of 167 kMs. One of the solutions offered is the need to solve the feeder and plan for the construction of the Monta switch substation to reduce the load and length of the Karumbu feeder by simulating using ETAP 12.6.0 software. Based on the simulation results using the ETAP 12.6.0 software, the voltage at the end of the Karumbu feeder was obtained from 18.087 kV to 18.885 kV after solving the feeder load. The benefits that will be obtained later are reducing the burden on the Karumbu feeder and improving the voltage on the 20 kV and customer sides.